Role of Emotional Intelligence in Genders' Career Advancement - Fida, Farah; Akhter, Nasreen; Bukhari, Syeda Tehmina Naz (The journal of contemporary issues in business and government, 2022)
This study examined the role of Emotional Intelligence (EI)in genders’career advancement.Data was collected from male and female faculty members of The Islamia University of Bahawalpur and Bahudin Zakria University of Punjab in order to achieve the research goal. Six departments of social sciences and six departments of pure sciences were chosen for this purpose. Data was collected from 180 female and 120 male faculty members. The analysis was created using Daniel Goleman's EI concept to assess EI. The Self-Report Measure of EI (SRMEI) questionnaire was used to collect data. SPSS was used to analyze the data by deployingthe independent samples t- test. The outcomes of the study indicated a positive association between EI and genders’ career advancement. Furthermore, the outcomes indicated that male faculty members are more emotionally intelligent than female faculty members.